Job satisfaction,quality of work life and general mental health of the employee - Ruso, Ester (My University, 1993)
unknown
Keywords: Ekonomi; Emek ekonomisi; İŞGÜCÜ-ÇALIŞMA HAYATI-SAĞLIK; ÖRGÜTSEL DAVRANIŞ-İŞ TATMİNİ